Efficacy of eculizumab in an adult patient with HIV-associated hemolytic uremic syndrome: A case report. Issue 51 (December 2017) - Freist, Marine; Garrouste, Cyril; Szlavik, Nora; Coppo, Paul; Lautrette, Alexandre; Heng, Anne Elisabeth
Abstract: Introduction: Hemolytic uremic syndrome (HUS) in Human Immunodeficiency Virus (HIV)-positive patients has become a rare cause of kidney injury since the era of highly active antiretroviral therapy (HAART). Plasma exchange and antiretroviral therapy were previously recommended but often failed to achieve remission. We report a case of HUS in a HIV-positive patient treated successfully with eculizumab. Case summary: A 52-year-old woman presented to hospital with acute renal failure, thrombocytopenia, anemia, and hypoxemia. She had been diagnosed with HIV infection in 1997. Kidney biopsy showed several fibrinous microthrombi in the glomerular capillaries, formation of thrombi in arterioles, moderate parietal and mesangial deposits of C3 and Immunoglobulin M, and intense glomerular and arterial deposits of Complement component 5b9 complement component. Serum HIV viral load was 227, 848 copies/mL, and CD4 lymphocyte count was 120 cells/μL. A diagnosis of HIV-associated HUS was made. The patient had no confounding cause of HUS. Initiation of eculizumab and HAART resulted in complete hematological remission on day 32 and dialysis withdrawal on day 110. The patient has not relapsed during long-term follow-up (M17). Conclusion: This observations uggests that eculizumab can achieve remission in HIV patients with HUS.